Development of Teaching Modules Based on Gresik Local Wisdom for Science Subjects Class IV UPT SDN 68 Gresik - Fatimah, Siti; Setyawan, Agung; Ulva Rahmi, Ulva Rahmi (eductum: Jurnal Literasi Pendidikan, 2025)
The objectives of this development research are to (1) develop a teaching module based on Gresik local wisdom for science subjects class IV UPT SDN 68 Gresik that is valid based on expert validation. (2) developing teaching modules based on Gresik local wisdom for science subjects class IV UPT SDN 68 Gresik that are effective based on posttest scores as well as observation results. (3) developing a teaching module based on Gresik local wisdom for science subjects class IV UPT SDN 68 Gresik that is interesting based on student responses. This study uses the ADDIE model. This research was conducted in class IV UPT SDN 68 Gresik. The validity of the module is obtained from the results of the validity of the material, teaching materials, and learning design. Based on the data obtained by the researcher, the results of the material validity test were 93.34% with the "High" category, the validity of teaching materials was 80.00% with the "High" validity category, and the validity of the learning design was 87.50% with the "High" validity category. Based on the Aiken validity index, a validity coefficient of 86.96% was obtained. Based on the results of data analysis, it is known that the validity of material items, teaching materials, and learning designs received a score of 86 so that it can be concluded that the validation results in this study are "Valid". The attractiveness of the module was obtained from the value of the student response questionnaire with a percentage of 84.625% with the category of "Very Interesting". Meanwhile, in the effectiveness of the module, the result of classical completeness was obtained by 100%, the development module received the "Effective" category.